2022
DOI: 10.24191/jscet.v1v2.63-77
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Earth Fill Dam under Earthquake Load Using Finite Element Method: A Case Study of Semenyih Dam

Abstract: In this project, an earth-fill dam in Selangor which is Semenyih Dam, a major dam in the Klang Valley with a capacity of 60.6 million cubic metres, a height of 49 metres, and a crest length of reservoir embankment of 830 metres, is being used as a study subject. The Finite Element Method was used in this work to assess the stress and deformation of Semenyih Dam, an earth dam in Selangor that was resting under hydrostatic pressure. The second objective is to study the Semenyih dam’s seismic response due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…As the value of stresses is acceptable, it can be said that the dam can withstand the load applied and exert maximum stresses lower than allowable capacity. The results obtained in this study agreed well with that reported by Ismail et al [9].…”
Section: Stress Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…As the value of stresses is acceptable, it can be said that the dam can withstand the load applied and exert maximum stresses lower than allowable capacity. The results obtained in this study agreed well with that reported by Ismail et al [9].…”
Section: Stress Analysissupporting
confidence: 93%
“…Enhancement on the material performance for the application due to seismic effect was conducted in prevoius studies [4]- [8]. Furthermore, many studies have been made to mitigate the seismic responses of dams [9]- [13], buildings [14]- [18] and bridges [19]- [20] due to seismic loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact of earthquakes is one of the major concerns of scientists and engineers for a long time. Many studies have been made to mitigate the seismic responses of structures due to seismic loads [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%